Ru-doped porous Co3O4 nano material as well as preparation method and application thereof
By doping Ru in Co3O4 nanomaterials, the problems of poor structural tolerance and small number of active sites in Ru-doped Co3O4 materials in the existing technology are solved, and Ru-doped porous Co3O4 with high stability and catalytic performance is achieved. Preparation of nanomaterials.
Patent Information
- Application Number
- CN202411433839.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
AI Technical Summary
The existing Ru-doped Co3O4 material preparation method cannot retain the original Co-MOF morphology. Ru is only doped on the Co3O4 surface, resulting in poor structural tolerance and small number of active sites, and thus poor catalytic stability.
A first solvothermal reaction was performed by mixing a cobalt source, 3,3',4,4'-biphenyltetracarboxylic acid and a polar organic solvent to form the coordination polymer Co-BPTC, and then a second reaction was performed with ethanol and a ruthenium source. Through solvothermal reaction, Ru-doped Co-BPTC is obtained, and Ru-doped porous Co3O4 nanomaterials are obtained through oxidation and calcination.
This method effectively retains the original rod-like morphology of MOF, anchors Ru(III) ions, improves the stability and catalytic performance of Ru-doped porous Co3O4 nanomaterials, increases structural tolerance and the number of active sites, and improves electrocatalytic stability. also significantly improved.
Smart Images

Figure CN119327481A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous micro-nano materials, and specifically relates to a Ru-doped porous Co3O4 nano material and a preparation method and application thereof. Background Art
[0002] Transition metal oxides can provide chemical adsorption sites for oxygen in OER (oxygen evolution reaction), and mixed valence states also play an important role in the electrocatalytic process. Combined with their excellent corrosion resistance, they have become electrocatalytic materials with development potential. In particular, Co3O4 has been developed as a high-performance OER catalyst to replace precious metal-based catalysts (such as IrO2 and RuO2) due to its adjustable nanostructure, high activity and thermodynamic stability. However, Co3O4-based electrocatalysts face the disadvantages of limited number of active sites and poor structural stability under harsh OER conditions.
[0003] Noble metal oxides such as IrO2 and RuO2 intrinsically exhibit superior OER activity. However, they are limited by their scarcity and structural instability under continuous operating conditions, which greatly restricts their practical applications.
[0004] In order to maximize the use of precious metal atoms and improve the catalytic performance of Co3O4 catalysts, the currently commonly used and effective strategy is to embed precious metals into Co3O4, which can improve both the catalytic performance and the catalyst stability. In the prior art, the common preparation method of Ru-doped Co3O4 materials cannot retain the original Co-MOF morphology, and Ru is only doped on the surface of Co3O4, resulting in poor structural tolerance of the final product, a small number of active sites, and poor catalytic stability. At present, it is still a huge challenge to improve the catalytic performance of Co3O4 catalysts by rationally designing porous nanostructures combined with precious metal Ru. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a Ru-doped porous Co3O4 nanomaterial and its preparation method and application. The preparation method provided by the present invention can effectively retain the original rod-shaped morphology of MOF, effectively anchor Ru(III) ions, and the Ru-doped porous Co3O4 nanomaterial has high stability.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing Ru-doped porous Co3O4 nanomaterial, comprising the following steps:
[0008] After mixing the cobalt source, 3,3',4,4'-biphenyltetracarboxylic acid and a polar organic solvent, adjusting the pH value to acidic, and performing a first solvothermal reaction, the Co ions and 3,3',4,4'-biphenyltetracarboxylic acid undergo coordination self-assembly to obtain a coordination polymer Co-BPTC;
[0009] The Co-BPTC, ethanol and a ruthenium source are mixed to perform a second solvothermal reaction to obtain Ru-doped Co-BPTC;
[0010] The Ru-doped Co-BPTC is subjected to oxidation calcination to obtain the Ru-doped porous Co3O4 nanomaterial.
[0011] Preferably, the cobalt source comprises one or more of cobalt acetate, cobalt chloride, cobalt sulfate and cobalt nitrate;
[0012] The molar ratio of the cobalt source to 3,3',4,4'-biphenyltetracarboxylic acid is 10-15:4-6.
[0013] Preferably, the polar organic solvent comprises N-methylformamide and / or ethanol;
[0014] The volume ratio of the molar amount of the cobalt source to the polar organic solvent is 0.10-0.15 mmol:1-5 mL.
[0015] Preferably, when the polar organic solvent uses N-methylformamide and ethanol, the volume ratio of N-methylformamide to ethanol is 1 to 3:1.
[0016] Preferably, the temperature of the first solvothermal reaction and the second solvothermal reaction are independently 130-150° C., and the time is independently 2-8 hours.
[0017] Preferably, the ruthenium source is ruthenium chloride;
[0018] The mass ratio of the Co-BPTC to the ruthenium in the ruthenium source is 100:1-15.
[0019] Preferably, the temperature of the oxidation calcination is 320-380°C and the time is 4-10h;
[0020] The calcination is performed in an air atmosphere.
[0021] The present invention also provides a Ru-doped porous Co3O4 nanomaterial prepared by the preparation method described in the above technical solution, comprising a porous Co3O4 nanomaterial and Ru atoms doped in the porous Co3O4 nanomaterial.
[0022] Preferably, the mass content of Ru in the Ru-doped porous Co3O4 nanomaterial is 0.5-10%.
[0023] The present invention also provides the application of the Ru-doped porous Co3O4 nanomaterial described in the above technical solution in OER catalysts.
[0024] The invention provides a preparation method of Ru-doped porous Co3O4 nanomaterial, comprising the following steps: mixing a cobalt source, 3,3',4,4'-biphenyltetracarboxylic acid and a polar organic solvent, adjusting the pH value to acidic, performing a first solvothermal reaction, and allowing Co ions to coordinate and self-assemble with 3,3',4,4'-biphenyltetracarboxylic acid to obtain a coordination polymer Co-BPTC; mixing the Co-BPTC, ethanol and a ruthenium source, performing a second solvothermal reaction, and obtaining Ru-doped Co-BPTC; and oxidatively calcining the Ru-doped Co-BPTC to obtain the Ru-doped porous Co3O4 nanomaterial. The invention uses Co as a central metal ion and 3,3',4,4'-biphenyltetracarboxylic acid (H4BPTC) as a ligand. Under solvothermal conditions, the metal ion Co and the organic ligand H4BPTC are interconnected by self-assembly to form a type of crystalline porous material Co-BPTC with a periodic network structure, wherein the Co-BPTC asymmetric unit comprises half of a cobalt ion and a quarter of a deprotonated BPTC4-linker, which is combined with eight Co(II) centers through four carboxylic acid groups, and the hexacoordinated Co(II) cation is composed of four carboxylic acid oxygen atoms and two solvent oxygen atoms to form a slightly distorted square bipyramid; the obtained Co-BPTC has multiple adsorption sites in structure and is stable in structure, and can effectively anchor Ru(III) on the surface, inside and in the pores. ) ions, making it an ideal precursor for Ru-doped porous nanomaterials. In related technologies, after the metal organic ligand anchors the Ru ions, calcination will cause the original morphology of MOF to change, which will affect the catalytic performance and stability of the catalyst; the precursor is subjected to high-temperature oxidation to obtain Ru-doped porous Co3O4 nanomaterials derived from MOF (referred to as Ru-Co3O4 materials), which maintain the original morphology of the precursor, and Ru is dispersed in the porous Co3O4 material in the form of atoms. The Ru in the Co3O4 material replaces part of the Co, which enhances the electron delocalization around the Co atoms, changes the bonding environment around the Co center, adjusts the surface electron distribution, avoids significant potential-determined surface reconstruction, improves the structural tolerance of the nanomaterial, and thus improves the stability of the nanomaterial.
[0025] Co3O4 derived from Co-BPTC retains the characteristics of porosity, has a large specific surface area, increases the contact area of the oxygen evolution reaction, and Ru and Co are the active sites of the reaction, Ru has good dispersibility and high atomic utilization. The substitution of Ru in Co3O4 can be transferred from Ru atoms to adjacent Co atoms through bridging oxygen bonds. Since the relatively electron-deficient Ru-O-Co unit with a strong electron coupling effect can drag electrons from adjacent electron-rich Co sites through bridging oxygen bonds during the OER electrocatalysis, it can effectively prevent the over-oxidation of active Ru and Co sites, thereby maintaining the durability of OER. Therefore, the introduction of Ru atoms significantly improves the structural tolerance of Co3O4 and inhibits the structural reconstruction of Co species in Co3O4 during water oxidation. It can be seen from the test results that the Ru-Co3O4 porous nanomaterial provided by the present invention has a regular morphology, a rod-like structure, a large specific surface area, a high porosity, and a high electrocatalytic stability; after 1000 CV scans, the LSV curve changes differ by 7mV. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0027] Figure 1 This is a schematic diagram of the process of preparing Ru-doped porous Co3O4 nanomaterials in Example 1;
[0028] Figure 2 This is the SEM image of the rod-shaped porous CoOF-1 prepared in Example 1;
[0029] Figure 3 This is a SEM image of Ru-CoOF-1 prepared in Example 1;
[0030] Figure 4 XRD patterns of CoOF-1 and Ru-CoOF-1 prepared in Example 1;
[0031] Figure 5 Digital photos of CoOF-1 and Ru-CoOF-1 prepared in Example 1;
[0032] Figure 6 FT-IR images of CoOF-1 and Ru-CoOF-1 prepared in Example 1;
[0033] Figure 7 BET diagram and pore size distribution PSD curve diagram of CoOF-1 and Ru-CoOF-1 prepared in Example 1;
[0034] Figure 8 SEM (a), HR-TEM (b) and HAADF-STEM (c) images of Ru-Co3O4 prepared in Example 1;
[0035] Fig. 9 XRD diagrams of Ru-Co3O4 prepared in Example 1 and Co3O4 obtained in Comparative Example 1;
[0036] Fig.10 The Raman graphs of Ru-Co3O4 prepared in Example 1 and Co3O4 obtained in Comparative Example 1;
[0037] Fig.11 The nitrogen adsorption-desorption curve and pore size distribution PSD curve of Ru-Co3O4 prepared in Example 1;
[0038] Fig.12 LSV curve (a), Tafel slope (b), Cdl curve (c), EIS curve (d), LSV curve before and after 1000 cycles of CV (e) and IT stability test (f) of the Ru-Co3O4 prepared in Examples 1 to 3 and the catalysts obtained in Comparative Examples 1 to 2;
[0039] Fig.13 are the different molecular structures in the nanomaterial prepared in Example 2 and the adsorption energies corresponding to the different molecular structures;
[0040] Fig.14 The XPS graphs of the nanomaterials prepared in Example 2 and Comparative Examples 1-2;
[0041] Fig.15 This is the electron distribution model of the Ru-Co3O4 nanomaterial prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0042] The present invention provides a method for preparing Ru-doped porous Co3O4 nanomaterial, comprising the following steps:
[0043] After mixing the cobalt source, 3,3',4,4'-biphenyltetracarboxylic acid and a polar organic solvent, adjusting the pH value to acidic, and performing a first solvothermal reaction, the Co ions and 3,3',4,4'-biphenyltetracarboxylic acid undergo coordination self-assembly to obtain a coordination polymer Co-BPTC;
[0044] The Co-BPTC, ethanol and a ruthenium source are mixed to perform a second solvothermal reaction to obtain Ru-doped Co-BPTC;
[0045] The Ru-doped Co-BPTC is subjected to oxidation calcination to obtain the Ru-doped porous Co3O4 nanomaterial.
[0046] In the present invention, unless otherwise specified, the raw materials involved are commercially available products known in the art.
[0047] The invention mixes a cobalt source, 3,3',4,4'-biphenyltetracarboxylic acid and a polar organic solvent, adjusts the pH value to acidic, performs a first solvent thermal reaction, and the Co ions and the 3,3',4,4'-biphenyltetracarboxylic acid undergo coordination self-assembly to obtain a coordination polymer Co-BPTC.
[0048] In the present invention, the cobalt source preferably includes one or more of cobalt acetate, cobalt chloride, cobalt sulfate and cobalt nitrate. In a specific embodiment, the cobalt source can be cobalt acetate, cobalt chloride, cobalt sulfate or cobalt nitrate. In the present invention, the molar ratio of the cobalt source to 3,3',4,4'-biphenyltetracarboxylic acid is preferably 10-15:4-6. In a specific embodiment, the molar ratio of the cobalt source to 3,3',4,4'-biphenyltetracarboxylic acid can be 10:4, 12:5, 14:5 or 15:6.
[0049] In the present invention, the polar organic solvent preferably includes N-methylformamide and / or ethanol. In a specific embodiment, the polar organic solvent can be N-methylformamide, ethanol, or N-methylformamide and ethanol. In the present invention, when the polar organic solvent uses N-methylformamide and ethanol, the volume ratio of N-methylformamide to ethanol is preferably 1 to 3:1. In a specific embodiment, the volume ratio of N-methylformamide to ethanol can be 1:1, 2:1 or 3:1.
[0050] In the present invention, the volume ratio of the molar amount of the cobalt source to the polar organic solvent is preferably 0.10-0.15 mmol:1-5 mL. In a specific embodiment, the volume ratio of the molar amount of the cobalt source to the polar organic solvent can be 0.10 mmol:1 mL, 0.11 mmol:2 mL, 0.12 mmol:3 mL, 0.13 mmol:4 mL or 0.15 mmol:5 mL.
[0051] In the present invention, nitric acid is preferably used to adjust the pH value to acidic, the concentration of the nitric acid is preferably 65-75wt%, and the volume of the nitric acid is preferably 0.2-0.5mL. The present invention does not specifically limit the specific pH value, and it can be adjusted to acidic.
[0052] In the present invention, the temperature of the first solvent thermal reaction is preferably 130-150°C, and in a specific embodiment, the temperature of the first solvent thermal reaction can be 130°C, 140°C or 150°C; the time is preferably 2-8h, and in a specific embodiment, the time of the first solvent thermal reaction can be 2h, 4h, 6h or 8h. In the first solvent thermal reaction, the cobalt source is coordinated with 3,3',4,4'-biphenyltetracarboxylic acid to obtain Co-BPTC.
[0053] In the present invention, after the first solvent thermal reaction, the process preferably further includes solid-liquid separation, solid washing and drying of the obtained product liquid.
[0054] The present invention has no special requirements for the method of solid-liquid separation, and the commonly used technical means in the art can be used. In the specific embodiment of the present invention, centrifugal method is used for solid-liquid separation. This means is a conventional means, and the subsequent operation is the same as this operation, and will not be explained later.
[0055] The present invention has no special requirements for the washing method, and the commonly used technical means in the art can be used. In a specific embodiment of the present invention, ethanol is used for washing, preferably 2 to 3 times. This means is a conventional means, and the subsequent operations are the same as this operation, and will not be explained later.
[0056] The present invention has no special requirements for the drying method, and the commonly used technical means in the art can be used. In a specific embodiment of the present invention, the washed product is placed in a vacuum dryer at 85° C. for drying. This means is a conventional means, and the subsequent operations are the same as this operation, and will not be explained later.
[0057] After obtaining the Co-BPTC, the present invention mixes the Co-BPTC, ethanol and a ruthenium source to perform a second solvothermal reaction to obtain Ru-doped Co-BPTC.
[0058] In the present invention, mixing the Co-BPTC, ethanol and a ruthenium source preferably comprises: dissolving the ruthenium source in part of the ethanol to obtain a ruthenium source ethanol solution; mixing the Co-BPTC with the remaining ethanol, and then adding the ruthenium source ethanol solution to the resulting mixture.
[0059] In the present invention, the ruthenium source is preferably ruthenium chloride. In the present invention, the concentration of Ru in the ruthenium source ethanol solution is preferably 3 to 8 mg / mL. In a specific embodiment, the concentration of Ru in the ruthenium source ethanol solution can be 3 mg / mL, 5 mg / mL, 6 mg / mL or 8 mg / mL.
[0060] In the present invention, the mass ratio of the Co-BPTC to the ruthenium in the ruthenium source is preferably 100:1 to 15. In a specific embodiment, the mass ratio of the Co-BPTC to the ruthenium in the ruthenium source can be 100:1, 100:3, 100:5, 100:10, 100:12 or 100:15. In the present invention, the mass ratio of the Co-BPTC to the volume of the remaining ethanol is preferably 30 mg:3 to 10 mL. In a specific embodiment, the mass ratio of the Co-BPTC to the volume of the remaining ethanol can be 30 mg:3 mL, 30 mg:5 mL, 30 mg:8 mL or 30 mg:10 mL.
[0061] In the present invention, the temperature of the second solvent thermal reaction is preferably 130-150°C. In a specific embodiment, the temperature of the second solvent thermal reaction can be 130°C, 140°C or 150°C; the time is preferably 2-8h. In a specific embodiment, the time of the second solvent thermal reaction can be 2h, 4h, 6h or 8h. In the second solvent thermal reaction, the unique Co-BPTC obtained captures Ru ions at multiple sites in the pores, the edges of the Co-O chains, and the Co-O chain lattices, so that Ru is not only anchored on the surface of Co-BPTC, but also anchored in the pores and lattices of Co-BPTC. This is also the most essential difference between the present invention and other related technologies. The unique Co-BPTC MOF selected by the present invention can effectively and multi-site capture Ru ions, greatly improving the number and dispersion of Ru active sites, while other MOFs are limited to surface adsorption.
[0062] In the present invention, after the second solvent thermal reaction, the process preferably further includes solid-liquid separation, solid washing and drying of the obtained product liquid.
[0063] After obtaining the Ru-doped Co-BPTC, the present invention performs oxidation calcination on the Ru-doped Co-BPTC to obtain the Ru-doped porous Co3O4 nanomaterial.
[0064] In the present invention, the temperature of the oxidation calcination is preferably 320-380°C. In a specific embodiment, the calcination temperature can be 320°C, 340°C, 360°C or 380°C; the time is preferably 4-10h. In a specific embodiment, the oxidation calcination time can be 4h, 6h, 8h or 10h. In the present invention, the oxidation calcination is preferably carried out in an air atmosphere. In the present invention, the heating rate to the calcination temperature is preferably 3-8°C / min. In a specific embodiment, the heating rate can be 3°C / min, 5°C / min and 8°C / min. During the oxidation calcination process, in the presence of oxygen, Co-BPTC is calcined into a porous Co3O4 nanomaterial, ruthenium chloride is converted into Ru nanoparticles, and replaces part of the Co nanoparticles to obtain a Ru-doped porous Co3O4 nanomaterial.
[0065] The present invention uses Co as a central metal ion and 3,3',4,4'-biphenyltetracarboxylic acid (H4BPTC) as a ligand. Under solvothermal conditions, the metal ion Co and the organic ligand H4BPTC are interconnected by self-assembly to form a type of crystalline porous material Co-BPTC with a periodic network structure, wherein the Co-BPTC asymmetric unit contains half of a cobalt ion and a quarter of a deprotonated BPTC4-linker, which is combined with eight Co(II) centers through four carboxylic acid groups, and the hexacoordinated Co(II) cation is composed of four carboxylic acid oxygen atoms and two solvent-based oxygen atoms to form a slightly distorted square bipyramid; the obtained Co-BPTC has multiple adsorption sites in structure and is stable in structure, and can effectively anchor Ru(III) ions, so that It is an ideal precursor for Ru-doped porous nanomaterials. In related technologies, after metal organic ligands anchor Ru ions, calcination will cause the original morphology of MOF to change, which will affect the catalytic performance and stability of the catalyst. The precursor is subjected to high-temperature oxidation to obtain Ru-doped porous Co3O4 nanomaterials derived from MOF (referred to as Ru-Co3O4 materials), which maintain the original morphology of the precursor. Ru is dispersed in the porous Co3O4 material in atomic form. The Ru in the Co3O4 material replaces part of Co, which enhances the electron delocalization around the Co atoms, changes the bonding environment around the Co center, adjusts the surface electron distribution, avoids significant potential-determined surface reconstruction, improves the structural tolerance of the nanomaterial, and thus improves the stability of the nanomaterial.
[0066] The present invention also provides a Ru-doped porous Co3O4 nanomaterial prepared by the preparation method described in the above technical solution, comprising a porous Co3O4 nanomaterial and Ru atoms doped in the porous Co3O4 nanomaterial.
[0067] In the present invention, the porous Co3O4 nanomaterial is a rod-shaped structure. The present invention uses the coordination polymer Co-BPTC as a precursor of Co3O4. The Co-BPTC structure is stable and has a rod-shaped structure. After being doped with Ru and oxidized and calcined, the rod-shaped porous Co3O4 nanomaterial can still be maintained, thereby forming a rod-shaped porous Co3O4 nanomaterial.
[0068] In the present invention, the mass content of Ru in the Ru-doped porous Co3O4 nanomaterial is preferably 0.5-10%. In a specific embodiment, the mass content of Ru in the Ru-doped porous Co3O4 nanomaterial can be 0.5%, 1.5%, 2%, 3%, 3.5%, 5%, 6%, 8% or 10%. In the present invention, the specific surface area of the Ru-doped porous Co3O4 nanomaterial is preferably 30-36 m 2 ·g -1 The pore size is preferably 0.8 to 4 nm.
[0069] The present invention also provides application of the Ru-doped porous Co3O4 nanomaterial in OER catalyst.
[0070] The present invention has no special requirements on the method of the application, and the commonly used technical means in the field can be adopted.
[0071] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in conjunction with specific embodiments below. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Any modification, equivalent replacement, improvement, etc. made to the implementation methods of the present invention based on the technical essence and general principles of the present invention without creative work should be within the scope of protection of the present invention.
[0072] Example 1
[0073] Example 1 Preparation process of Ru-doped porous Co3O4 nanomaterials, such as Figure 1 shown.
[0074] 0.12mmol cobalt acetate Co(CH3COO)2, 0.05mmol 3,3',4,4'-biphenyltetracarboxylic acid (H4BPTC), 2mL N-methylformamide (NMF) and 1mL ethanol (EtOH) were mixed and added to a 35mL pressure tube, 0.3mL 70wt% nitric acid was added to adjust the pH to acidic, and placed in an aluminum block bath at 140°C and 500rpm for 4h. After cooling to room temperature, centrifugation was performed, washed and filtered 3 times with ethanol, and the solid was placed at 85°C for vacuum drying to obtain Co-BPTC, which was recorded as CoOF-1.
[0075] After mixing 30 mg CoOF-1 with 3 mL ethanol, 0.06 mL 5 mg / mL RuCl3 ethanol solution was added, placed in an oven, and heated to 140°C at a heating rate of 1°C / min for 6 hours. After cooling to room temperature, centrifugation was performed, washed and filtered three times with ethanol, and the solid was placed at 85°C and vacuum dried to obtain Ru-doped Co-BPTC, which was recorded as Ru-CoOF-1.
[0076] Ru-CoOF-1 was placed on a quartz boat, placed in a muffle furnace, heated to 350°C at a heating rate of 5°C / min, calcined in air for 6 hours, and cooled to room temperature to obtain Ru-doped porous Co3O4 nanomaterials, recorded as Ru-Co3O4-1. The Ru loading in Ru-Co3O4-1 was determined to be 0.52wt% by ICP-OES.
[0077] The CoOF-1 obtained in Example 1 was scanned under a scanning electron microscope to obtain Figure 2 The Ru-CoOF-1 obtained in Example 1 was scanned under a scanning electron microscope to obtain Figure 3 .from Figure 2 , 3 It can be seen that the rod-like structure of CoOF-1 remains unchanged before and after Ru doping.
[0078] The CoOF-1 and Ru-CoOF-1 prepared in Example 1 were subjected to X-ray diffraction analysis to obtain Figure 4 .from Figure 4 It can be seen that the spectra obtained for Ru-CoOF-1 and CoOF-1 match the simulated PXRD patterns, and the diffraction peaks at 8.1°, 15.1°, and 16.9° correspond to the sharp diffraction peaks of the (110), (211), and (220) planes, respectively, indicating that high-purity and high-crystallinity MOF materials have been synthesized.
[0079] The morphologies of CoOF-1 and Ru-CoOF-1 prepared in Example 1 are observed. Figure 5 As shown in Figure 2, from CoOF-1 to Ru-CoOF-1, the powder color changes from pink to dark pink, proving the successful doping of Ru.
[0080] The CoOF-1 and Ru-CoOF-1 prepared in Example 1 were subjected to infrared analysis. Figure 6 As shown. It can be seen that at 1560cm -1 、1420cm -1 、1180cm -1 and 484cm -1There are 4 characteristic peaks at the bottom, which correspond to the stretching vibrations of C=O, C=C, CO and MO. These bonds correspond to the structure of CoOF-1, and the peaks do not change before and after Ru incorporation, indicating that its structure has not changed.
[0081] The CoOF-1 and Ru-CoOF-1 prepared in Example 1 were subjected to BET test and pore size analysis, and the results were Figure 7 .from Figure 7 As shown in the figure, the nitrogen adsorption-desorption curve of CoOF-1 is a type IV adsorption curve, which is a typical adsorption-desorption isotherm of non-porous materials. Its pore size distribution (PSD) is narrowly distributed in the 5nm region. After Ru is loaded on the surface of CoOF-1, the BET value increases from 46.4 nm to 5 nm. 2 ·g -1 Down to 34.4m 2 ·g -1 , the pore sizes are mainly between 0.8 and 4 nm, indicating that the introduction of Ru can effectively occupy the MOF pores.
[0082] The Ru-Co3O4-1 prepared in Example 1 was scanned under a scanning electron microscope, a transmission electron microscope and a high-angle annular dark field scanning transmission electron microscope to obtain Figure 8 .like Figure 8 As shown in the figure, after calcining Ru-CoOF-1, the rod-like morphology remains unchanged, and the 0.295nm of the lattice fringes is attributed to the (220) crystal plane exposed by Co3O4. From the HAADF-STEM image, it can be seen that Ru atoms (marked with red circles) are successfully loaded and dispersed on the porous Co3O4 substrate.
[0083] The Ru-Co3O4-1 prepared in Example 1 was subjected to BET test and pore size analysis. Fig.11 The BET of Ru-Co3O4 is 37.6m 2 ·g -1 The pore size distribution is between 1 and 5 nm, indicating its porosity.
[0084] Example 2
[0085] 0.3 mL of 5 mg / mL RuCl3 ethanol solution was added. The other conditions were the same as those in Example 1 to obtain Ru-Co3O4-5. The Ru loading in Ru-Co3O4-5 was determined by ICP-OES to be 3.05 wt%.
[0086] Example 3
[0087] 0.6 mL of 5 mg / mL RuCl3 ethanol solution was added. The other conditions were the same as those in Example 1 to obtain Ru-Co3O4-10. The Ru loading in Ru-Co3O4-10 was determined by ICP-OES to be 8.26 wt%.
[0088] Comparative Example 1
[0089] No RuCl3 ethanol solution was added. Other conditions were the same as those in Example 1 to obtain Co3O4.
[0090] Comparative Example 2
[0091] No CoOF-1 was added. Other conditions were the same as in Example 1, and RuO2 was obtained.
[0092] Fig. 9 The XRD diagrams of Ru-Co3O4-1 prepared in Example 1 and Co3O4 obtained in Comparative Example 1 are shown in FIG. Fig. 9 It can be seen that the two diffraction peaks at 31.3° and 37.0° belong to the (220) and (311) planes of Co3O4, respectively, and no new peaks appear in Ru nanoparticles, indicating that Ru still exists in atomic form.
[0093] Fig.10 The Raman graphs of Ru-Co3O4-1 prepared in Example 1 and Co3O4 obtained in Comparative Example 1 are shown in Figure 1. Fig.10 It can be seen that 195.9cm -1 、477.7cm -1 、518.7cm -1 、612.4cm -1 and 683.7cm -1 There are five bands at the tetrahedral CoO4 site, corresponding to the F 2g Vibration and A of the octahedral CoO6 site 1g Vibration. Relative to Co3O4, the peak of Ru-Co3O4 catalyst increases from 683.7 cm -1 Move to 680.0cm -1 , there is a slight blue shift, indicating the effect of Ru incorporation on the stretching vibration of Co-O bonds. Ru atoms replace part of Co, and it can be seen in Raman that A 1g The band is very sensitive to changes in octahedral cation vibrations and is related to the tetrahedral dependence of F 2g The bands show a more obvious peak shift, which means that Ru atoms prefer to be anchored in the octahedral position of Co3O-.
[0094] The Ru-Co3O4 catalysts obtained in Examples 1 to 3 and the catalysts obtained in Comparative Examples 1 to 2 were subjected to electrocatalytic tests, and the electrolyte was 1M KOH. Fig.12 .from Fig.12 As shown in (a), the optimized Ru-Co3O4-5 has a current density of 10 mA cm -2 When the overpotential is the lowest (η10), it is 260mV, which is significantly lower than Fig.12 (a) MOF-derived Co3O4 (360 mV), Ru-Co3O4-1 (319 mV), Ru-Co3O4-10 (281 mV) and commercial RuO2 (342 mV). Fig.12 As can be seen in (b), Ru-Co3O4-5 has the smallest Tafel slope of 84 mV / dec1, indicating higher reaction kinetics. In addition, the electrochemically active surface area (ECSA) was measured as Fig.12 As shown in (c), the Cdl value of the Ru-Co3O4-5 porous material is calculated to be 3.17 mF·cm -2 , significantly larger than Co3O4 (1.32mF·cm -2 )、Ru-Co3O4-1(1.58mF·cm -2 )、Ru-Co3O4-10(2.78mF·cm -2 ) and RuO2 (0.58mF·cm -2 ) The Cdl value of the porous material indicates that Ru-Co3O4-5 has a superior electrochemical active area and more catalytic active sites. Fig.12 (d) shows a semicircle diameter with a lower frequency range (13.5Ω), which is smaller than that of RuO2 (17.2Ω). Therefore, Ru atoms help provide more active sites and faster charge transfer, thereby greatly improving the OER performance. After continuous 1000CV scanning, the LSV curve change of Ru-Co3O4-5 is negligible, with only 7mV ( Fig.12 (e)). Fig.12 As shown in (f), after 20 h of electrolysis, Ru-Co3O4-5 retained 95.8% of the initial current, while undoped Co3O4 and commercial RuO2 retained 71.4% and 80.6%, respectively.
[0095] Fig.13 The different molecular structures in the nanomaterials prepared in Example 2 and the adsorption energies corresponding to the different molecular structures. From the test results, the positive trivalent ruthenium ions are not only anchored on the surface of the material, but also anchored in the pores and lattices. The MOF CoOF-1 can effectively capture Ru ions at multiple sites, mainly at three sites: Ⅰ) in the pores of CoOF-1; Ⅱ) at the edge of the Co-O chain; Ⅲ) in the Co-O chain lattice, and this has been confirmed by theoretical calculations.
[0096] Fig.14The XPS graphs of the nanomaterials prepared in Example 2 and Comparative Examples 1-2 are shown in Figure 2. The high-resolution Co 2p spectrum shows that Co(II) has two fitting peaks at 781.2 and 796.4 eV, and Co(III) has two fitting peaks at 779.4 and 794.7 eV. As the electrons transfer from the Ru site to the Co site, the Co 2p 3 / 2 The binding energy of Ru-Co3O4 is positively shifted from 779.9eV to 780.5eV, indicating a strong electronic coupling effect. 2+ / Co 3+ The surface relative ratio (1.04) of Ru is supported, which is much higher than that of Ru-free Co3O4 (0.56). In the Ru 3p spectrum, the total binding energy of Ru-Co3O4 is 0.3eV higher than that of RuO2 and 0.5eV lower than that of RuCl3, indicating that the oxidation state of Ru in Ru-Co3O4 is between +3 and +4, which is higher than the original Co site (+3) in Co3O4.
[0097] Fig.15 This is the electron distribution model of the Ru-Co3O4 nanomaterial prepared in Example 2 of the present invention. In the Co3O4 model ( Fig.15 In a), the distribution of electrons is almost symmetrical, but after the introduction of Ru atoms, redistribution of electrons can be observed ( Fig.15 b). The preparation method provided by the present invention enhances the electron delocalization around the Co atom and changes the bonding environment around the Co center, avoiding significant potential-determined surface reconstruction. Therefore, the introduction of Ru atoms significantly improves the structural tolerance of Co3O4 and inhibits the structural reconstruction of Co species in Co3O4 during water oxidation.
[0098] The lowest overpotential and Tafel slope of the Ru-doped porous Co3O4 nanomaterial prepared in the prior art and the present invention are compared, and Table 1 is obtained.
[0099] Table 1 Comparison of the minimum overpotential and Tafel slope of Examples 1 to 3 and the prior art 1 to 3
[0100]
[0101] Note: Prior art 1: Journal of Colloid and Interface Science 606 (2022) 654-666; Prior art 2: Chemical Engineering Journal 420 (2021) 129805; Prior art 3: J. Mater. Chem. A, 2023, 11, 21767-21779
[0102] It can be seen from Table 1 that the Ru-Co3O4-5 prepared by the present invention has a minimum overpotential of 260 mV.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing Ru-doped porous Co3O4 nanomaterials, characterized in that: The following steps are involved: After mixing the cobalt source, 3,3',4,4'-biphenyltetracarboxylic acid and a polar organic solvent, adjusting the pH value to acidic, and performing a first solvothermal reaction, the Co ions and 3,3',4,4'-biphenyltetracarboxylic acid undergo coordination self-assembly to obtain a coordination polymer Co-BPTC; The Co-BPTC, ethanol and a ruthenium source are mixed to perform a second solvothermal reaction to obtain Ru-doped Co-BPTC; The Ru-doped Co-BPTC is subjected to oxidation calcination to obtain the Ru-doped porous Co3O4 nanomaterial.
2. The preparation method according to claim 1, characterized in that: The cobalt source includes one or more of cobalt acetate, cobalt chloride, cobalt sulfate and cobalt nitrate; The molar ratio of the cobalt source to 3,3',4,4'-biphenyltetracarboxylic acid is 10-15:4-6.
3. The preparation method according to claim 1, characterized in that: The polar organic solvent includes N-methylformamide and / or ethanol; The volume ratio of the molar amount of the cobalt source to the polar organic solvent is 0.10-0.15 mmol:1-5 mL.
4. The preparation method according to claim 3, characterized in that: When the polar organic solvent uses N-methylformamide and ethanol, the volume ratio of N-methylformamide to ethanol is 1 to 3:
1.
5. The preparation method according to claim 1, characterized in that: The temperature of the first solvothermal reaction and the second solvothermal reaction are independently 130-150° C., and the time is independently 2-8 hours.
6. The preparation method according to claim 1, characterized in that: The ruthenium source is ruthenium chloride; The mass ratio of the Co-BPTC to the ruthenium in the ruthenium source is 100:1-15.
7. The preparation method according to claim 1, characterized in that: The oxidation calcination temperature is 320-380°C and the time is 4-10h; The calcination is performed in an air atmosphere.
8. The Ru-doped porous Co3O4 nanomaterial obtained by the preparation method according to any one of claims 1 to 7 comprises a porous Co3O4 nanomaterial and Ru atoms doped in the porous Co3O4 nanomaterial.
9. The Ru-doped porous Co3O4 nanomaterial according to claim 8, characterized in that: The mass content of Ru in the Ru-doped porous Co3O4 nanomaterial is 0.5-10%.
10. Use of the Ru-doped porous Co3O4 nanomaterial according to any one of claims 8 to 9 in an OER catalyst.